IMPLEMENTING ISLAMIC BOARDING SCHOOL VALUES IN HUMAN RESOURCE PLANNING ON VOCATIONAL HIGH SCHOOL - Abdullah Aminuddin Aziz; Muhammad Al Fatih; Makhrus Aulia Izzul Haq (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2022)
Implementing human resource management at Vocational High School Khoiriyah is guided by Islamic boarding school values. The teachers at that school are very heterogeneous. The difference can be seen in the competence and mastery of technology. This study describes the human resource planning carried out by Vocational High School Khoiriyah Hasyim Tebuireng. The method used qualitatively with observations, interviews, and documentation for data collections. The results showed that human resource planning at Vocational High School Khoiriyah was carried out centrally in the quality assurance unit of the Islamic Boarding School. The results of human resource planning were approved by KH M Hasyim Asy’ari Foundation. The implementation of human resource planning at Vocational High School Khoiriyah, on enhancing teacher performance is based on Islamic Boarding School values by prioritizing cultural values. In the process, human resource planning also involves the business and industry for following the expertise program at Vocational High School Khoiriyah Tebuireng.